Representations of child solidarity in Guimarães Rosa and Mia Couto - Barbosa de Oliveira Neto, Francisco; Pereira Filha , Francisca do Nascimento (The ESPecialist, 2024)
This work aims to discuss the representations of children’s solidarity in the short stories A Menina de Lá, by Guimarães Rosa (2011), and A Menina sem Palavra, by Mia Couto (2018). To this end, it is based on bibliographical research and Comparative Literature, Short Story Theory and Childhood History. The results of the analysis demonstrate the difficulty of speech and interaction of the child characters with/in the family. The conclusion of the article is that the authors’ narratives represent voices, bodies and performances of previously silenced children, thus configuring possibilities for comparative reading of Brazilian and Mozambican literature.